RESPON AKTIVIS MUDA ACEH TERHADAP ISU ISLAM NUSANTARA DAN DINAMIKA SOSIAL MASYARAKAT - Rijal, Fakhrul; Muaamar, Muammar (PIONIR: JURNAL PENDIDIKAN, 2022)
The people of Aceh are most displeased with new things emerging from religion, especially in the name of Islam itself, such as Islam Nusantara. They will first vocally respond to Isnus without looking for details from the source. Especially young Acehnese activists. They are vocal about responding to their own version of Isnus, and mostly update their status on social media about developing issues. This research aims to map the response of young Acehnese activists to the issue of Indonesian Islam; finding the pattern of Indonesian Islam from the perspective of young Acehnese activists; explain the social dynamics of Acehnese society that emerged from the issue of Indonesian Islam; thus giving birth to characteristics or polarization of society with different criteria for the same issue. This research uses a qualitative approach. Data collection techniques in this research were carried out through participant observation, in-depth interviews and documentation studies. Interviews and observations were conducted with young Acehnese activists. The young Acehnese activists who were informants in this research were cadres of the Muhammadiyah organization, Nahdlatul Ulama, MIUMI, BKPRMI, HMI, PII, Rabithah Taliban Aceh (RTA). and explained to the public comprehensively so that they do not misunderstand Islam. If this is not done, then it would be better if there was no cultivation of Indonesian Islam. This view emerged from BKPRMI, KAMMI, HMI cadres.